UPBRINGING AND LEARNING UNITY AS A SOURCE FOR DEVELOPING TEACHERS' EMOTIONAL RESPONSIVENESS - Kusnere, Ilga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In the second half of the 20th century and the beginning of the 21st century, the scientific research in Europe started focusing more on the problems of upbringing. Pedagogical science was no exception, and also started raising questions regarding upbringing including both the teaching/learning and the upbringing/self-education processes in pedagogical activities and in the education system as a whole. The united way in which the teaching/learning, upbringing/self-education work is conducted at educational institutions reflects the professionalism of the teacher. The study reveals the necessity and importance of upbringing and unity in teaching work for the pedagogical processes of the 21st century.The study confirms that teachers’ knowledge, skills and attitude regarding education, teaching/learning, upbringing/self-education influences the obtainability of students’ achievements (Hattie, 2008, Hattie & Yates, 2013; Hattie & Zierer, 2018). The results of the research confirm the idea that the pedagogue has to invest in continuous development of professional competencies. The professional competence of the educator has a long-lasting impact on the individual's performance in learning and education processes as well as in their further life activities. Thus, the analysis of pedagogical theory and real-life practice shows that teaching and learning are the primary means for upbringing/self-education and performing the education functions in unity (Fišers, 2005, Hattie, 2008; Špona, 2018). In order to provide an acquisition of purposeful self-development management skills in pedagogical activities, a new approach and understanding of regularities is needed for the arrangement and management of educational learning processes.The aim of the study is to show the unity of teaching / learning, upbringing / self-education as an important approach in modern education.The main tasks are literary studies and evaluation, work with a target audience.Research methods: survey.